Workshop on maize seed health and seed testing for pests and pathogens - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2017)
Purpose and Objectives of the workshop: (i) To impart knowledge about major pests and pathogens of maize, risks to maize seed health, seed-borne pathogens, (ii) To inform about measures to control pests and disease and production of disease and pest-free seed (iii) To demonstrate laboratory methods for seed health testing